2016
DOI: 10.4236/fns.2016.72012
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Phytochemicals and Anti-Nutritional Factors in Some Selected Wild and Edible Bean in Nigeria

Abstract: This work aims at analyzing the bioactive and anti-nutritional compounds of edible and wild beans when unprocessed and malted. Qualitative screening of phytochemicals in the various bean samples was determined in ethanol and petroleum ether solvents. Results of the anti-nutritional compositions of unprocessed wild bean extracted with petroleum ether showed there were no traces of saponin and polyphenol, in Feregede and also in edible bean-IT07K-243-1-10 which also had no traces of saponin and tannin. After mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
1
4
0
1
Order By: Relevance
“…Generally, from Table 3, processing the seed will break down/deplete the antinutritional factors (except trypsin inhibitor) which otherwise inhibit protein digestibility. This is in agreement with the work of Awoyinka et al, [20] where malted legumes showed a decreased level of phytochemicals. Further on Table 3, the total Phenolics and DPPH increased after processing.…”
Section: Discussionsupporting
confidence: 93%
“…Generally, from Table 3, processing the seed will break down/deplete the antinutritional factors (except trypsin inhibitor) which otherwise inhibit protein digestibility. This is in agreement with the work of Awoyinka et al, [20] where malted legumes showed a decreased level of phytochemicals. Further on Table 3, the total Phenolics and DPPH increased after processing.…”
Section: Discussionsupporting
confidence: 93%
“…Approximately 1 mL of the supernatant was taken and 2,2'-Bipyridine solution (about 1.5 mL) added. Measurement of absorbance was then carried out at 420 nm against distilled water [23]. Trypsin measurement was carried out on the bases of extent of inhibition.…”
Section: Phytate Measurementmentioning
confidence: 99%
“…The residue was made to equilibrate for 30 mins after which the absorbances of the solutions were evaluated spectrophotometrically at 410 nm wavelength. An increase of 0.01 absorbance unit at 410 nm indicates one trypsin activity unit inhibition [23].…”
Section: Phytate Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…The wild bean has the highest phytic acid level compared to edible bean. The Nigerian bean showed varying levels of antinutrients when unprocessed but decreased marginally after malting [23].…”
Section: Antinutritional Composition Of Chickpea Genotypesmentioning
confidence: 99%